Expert Consensus on Nail Procedures and Selection of CPT Codes. Issue 8 (August 2021) - Baltz, Julia O.; Rubin, Adam; Adigun, Chris; Daniel, C. Ralph; Hinshaw, Molly; Knacksedt, Thomas; Lipner, Shari R.; Rich, Phoebe; Stern, Dana; Zaiac, Martin; Jellinek, Nathaniel J.
Abstract : BACKGROUND: Dermatologists specialize in treating conditions of the skin, hair, and nails; however, it is our experience that the field of nail diseases is the least discussed facet of dermatology. Even less acknowledged is the complexity of nail procedures and how best to accurately code for these procedures. OBJECTIVE: To convene a panel of experts in nail disease to reach consensus on the most accurate and appropriate Current Procedural Terminology (CPT) codes associated with the most commonly performed nail procedures. METHODS: A questionnaire including 9 of the most commonly performed nail procedures and potential CPT codes was sent to experts in the treatment of nail disease, defined as those clinicians running a nail subspecialty clinic and performing nail procedures with regularity. A conference call was convened to discuss survey results. RESULTS: Unanimous consensus was reached on the appropriate CPT codes associated with all discussed procedures. LIMITATIONS: Although this article details the most commonly performed nail procedures, many were excluded and billing for these procedures continues to be largely subjective. This article is meant to serve as a guide for clinicians but should not be impervious to interpretation in specific clinical situations. CONCLUSION: Billing of nail procedures remains a practice gap within our field. The authors hope that the expert consensus on the most appropriate CPT codes associated with commonly performed nail procedures will aid clinicians as they diagnose and treat disorders of the nail unit and encourage accurate and complete billing practices.